Rooting issue for a lattice fermion formulation similar to staggered fermions but without taste mixing - Adams, David H. (2013)
To investigate the viability of the 4th root trick for the staggered fermion determinant in a simpler setting, we consider a 2-taste (flavor) lattice fermion formulation with no taste mixing but with exact taste-nonsinglet chiral symmetries analogous to the taste-nonsinglet U(1) A symmetry of staggered fermions. Creutz’s objections to the rooting trick apply just as much in this setting. To counter them we show that the formulation has robust would-be zero modes in topologically nontrivial gauge backgrounds, and that these manifest themselves in a viable way in the rooted fermion determinant and also in the disconnected piece of the pseudoscalar meson propagator as required to solve the U(1) problem. Also, our rooted theory is heuristically seen to be in the right universality class for QCD if the same is true for an unrooted mixed fermion action theory.